Synthesis, structural characterisation and stereochemical investigation of chiral sulfur-functionalised N-heterocyclic carbene complexes of palladium and platinum - Krishnan, Deepa (2013)
Palladium and platinum complexes containing a sulfur-functionalised N-heterocyclic carbene (S-NHC) chelate ligand have been synthesised. The absolute conformations of these novel organometallic S-NHC chelates were determined by X-ray structural analyses and solution-phase 2D 1H–1H ROESY NMR spectroscopy. The structural studies revealed that the phenyl substituents on the stereogenic carbon atoms invariably take up the axial positions on the Pd-C-S coordination plane to afford a skewed five-membered ring structure. All of the chiral complexes are structurally rigid and stereochemically locked in a chiral ring conformation that is either (Rs,S,R)-λ or (Ss,R,R)-δ in both the solid state and solution.